تطوير متحكم عائم مرتكز على تقنية الاضطراب والمراقبة لتحسين كفاءة نظم الطاقة الشمسية الكهروضوئية باستخدام Matlab/Simulink - ديلانة إيمان (Latakia University Journal -Engineering Sciences Series, 2017)
يعالج هذا البحث تحسين كفاءة نظم القدرة الشمسية الكهروضوئية باستخدام متحكم عائم لتتبع نقطة الاستطاعة العظمى، للتحكم في دورة عمل مبدل جهد مستمر لتحقيق عمل النظام الكهروضوئي عند نقطة الاستطاعة العظمى في ظل التغيرات الجوية المختلفة من شدة إشعاع شمسي ودرجة حرارة محيطة. في هذا السياق، يقدم البحث نموذج جديد لمتحكم عائم MPPT-P&O Fuzzy مطور في بيئة Matlab/Simulink. يعتمد النموذج المقترح للمتحكم على تقنية الاضطراب والمراقبة P&O. حيث بطريقة مشابهة لتقنية P&O، تمثل كل من تغيرات الاستطاعة والتوتر للنظام الكهروضوئي، متغيرات دخل للمتحكم العائم المقترح، أما متغير الخرج فهو تغير نسبة التشغيل. الميزة الرئيسية للمتحكم العائم المطور، ترتكز على اعتبار أن خطوة تغير نسبة التشغيل ذات قيمة متغيرة ومتعلقة بشكل مباشر بتغيرات الاستطاعة والتوتر للنظام الكهروضوئي. مما يمكن من التغلب على مشكلة الخطوة الثابتة لتغير نسبة التشغيل في المتحكم MPPT-P&O المرتكز على تقنية P&O التقليدية. إن عمل المتحكم العائم MPPT-P& Fuzzy، بخطوة تشغيل متغيرة يحقق سرعة استجابة عالية وكفاءة عالية لتتبع نقطة MPP عند التغيرات الجوية المفاجئة أو السريعة، مقارنة مع المتحكم التقليدي .MPPT-P&O أظهرت نتائج المحاكاة المنجزة في بيئة Matlab/Simulink، الأداء الأفضل للمتحكم العائم المطور MPPT-P&O Fuzzy عند تتبع نقطة MPP بتحقيق أداء ديناميكي أفضل ودقة عالية، مقارنة مع استخدام المتحكم التقليدي MPPT-P&O عند التغيرات الجوية المختلفة. This research deals with improving the efficiency of solar photovoltaic (PV) power systems using a Fuzzy Logic Controller (FLC) for Maximum Power Point Tracking (MPPT), to control the duty cycle of DC-DC Voltage Converter, to achieve the photovoltaic system works at a Maximum Power Point under different atmospheric changes of the solar insolation and ambient temperature. In this context, this research presents a new model for FLC developed in Matlab/Simulink environment. The proposed model for the controller is based on the conventional Perturb and Observe (P&O) technique. Where, in similar to the conventional P&O technique, the changes in the Power and tension of photovoltaic power system, are considered as the input variables of the proposed controller, while the output variable is the change in the duty cycle. The main advantage of the developed controller FLC, based on the considering the change in the duty cycle has a Variable Step Size, and directly related to the changes in the power and tension of the Photovoltaic system. Which make it possible to overcome the problem of fixed Step Size in the change of the duty cycle in the conventional MPPT- P&O Controller based on P&O technique. The MPPT- P&O Fuzzy, works by a variable step size achieve a fast speed response and high efficiency for tracking the MPP point under sudden and rapidly varying atmospheric conditions, compared with the conventional MPPT- P&O. The simulation results completed in Matlab/Simulink environment, showed the best performance of developed MPPT- P&O Fuzzy controller in tracking the MPP by achieving a better dynamic performance and high accuracy, compared with the use of the conventional MPPT- P&O under different atmospheric changes.